Pengaruh Politik Terhadap Independensi Mahkamah Konsitusi Di Indonesia - Muhammad Egi Alkausar; Farhan Rizky Aria (CV. Multi Kreasi Media, 2025)
This study examines the impact of political dynamics on the independence of the Constitutional Court (MK), the guardian of the constitution in Indonesia. As an institution that should be free from interference, the MK is often vulnerable due to the tug-of-war of political interests, both in the recruitment process for constitutional judges, relations with other state institutions, and political pressure in handling strategic cases. This study uses a normative and analytical approach to assess the extent to which political influence can affect the MK's objectivity, integrity, and independence in carrying out its functions of judicial review, resolving election disputes, and upholding the principle of checks and balances. The analysis shows that political interference, both direct and indirect, can potentially undermine the independence of the constitutional court, necessitating the strengthening of the judicial selection mechanism, institutional transparency, and institutional reform. Overall, this study emphasizes the importance of maintaining the independence of the Constitutional Court to achieve a democratic and just constitutional system.